PRODUCTION OF PARTICLE BOARDS USING POLYSTYRENE AND BAMBOO WASTES (Nigerian Journal of Technology, 2017)
This investigation was able to produce incredibly strong particleboards using bamboo and resinous material obtained from Polystyrene wastes. The particleboards were prepared by mixing the bamboo fibres and Polystyrene based resin (PBR) followed by flat press process at different ratio (v/v). Physical properties were measured, with reference to normal and oven curing methods, according to the ASTM D-1037 standard. Thickness Swelling (TS) of the samples were measured after 2 and 24 hours of immersion in water at 25oC temperature. It was found that the physical properties of particleboards with 20%, 30% and 40% PBR content were all in agreement with low density particleboard classification of American National Standards Institute (ANSI). TS increased as the PBR content decreased in the matrix. Obtained properties convincingly indicate superior bonding ability of the synthesised resinous polystyrene over known industrial adhesives typically used for particleboard production. http://dx.doi.org/10.4314/njt.v36i3.18